Methotrexate Inhibits T Cell Proliferation but Not Inflammatory Cytokine Expression to Modulate Immunity in People Living With HIV - Freeman, Michael L.; Clagett, Brian M.; Moisi, Daniela; Yeh, Eunice; Morris, Charles D.; Ryu, Angela; Rodriguez, Benigno; Stein, James H.; Deeks, Steven G.; Currier, Judith S.; Hsue, Priscilla Y.; Anthony, Donald D.; et al. (Frontiers in Immunology, 2022)
In a placebo-controlled trial of low-dose methotrexate in ART-treated HIV infection, cycling (Ki67+) T cells lacking Bcl-2 were reduced by methotrexate but plasma inflammatory cytokines were largely unaffected. In vitro, methotrexate did not inhibit effector cytokine production but inhibited T cell proliferation downstream of mTOR activation, mitochondrial function, and cell cycle entry; this was reversible with folinic acid, suggesting low-dose methotrexate exerts anti-inflammatory effects in vivo largely by blocking T cell proliferation via dihydrofolate reductase inhibition, yet daily 1mg folate administration did not rescue this effect. Our findings identify the main mechanism of action of this widely used anti-inflammatory medicine.